The protection of the weak part of consumer relations information as an instrumental axis of protection and favor consumatore (2019)
The economic and social relationships of the present time are characterized by giving rise to situations in which one of the parties is in a position of subordination and therefore, of weakness. The consumer is a subject that presents this condition and the Law has responded to the protection requirements generating a special regime. The purpose of the article is to show the characteristics of the original imbalance of any consumer relationship and to emphasize that informative in equality plays a decisive role in it, whose existence has justified the intervention of the legislator to seek to re-establish balance. However, the giving of sector allaws may mean a risk in the proper application of the consumer protection regime if it is not based on an interpretation that prioritizes the application of the pro consumatore principle. © 2019, Universidad del Zulia. All rights reserved.